Peran Teknikal Objek dalam Membentuk Ruang Pembelajaran Sosial: Kasus Rumah Belajar ERBE - Alfiani, Kirana; Ekomadyo, Agus S.; Adhitama, Gregorius Prasetyo (Jurnal Sosioteknologi, 2024)
Technology integrates technical aspects with social, economic, political, and cultural aspects of human life, offering three layers of meaning: artifact, process, and knowledge. This research examines Rumah Belajar ERBE, a social learning space for impoverished communities, from a perspective known as social shaping of technology (SST). This research employs moment translation analysis, a technique derived from actor-network theory, to investigate the affordances that the learning space provides to the local community. This article explores the dynamic relationship between ERBE, which is composed of artifacts and activities, to understand the role of social technology in improving the lives of scavenger village residents. The findings reveal that the initiator and his house require proximity to ERBE to optimize the social learning process. Physical and functional affordances identified through the space's character and the use of non-fixed furniture make them multi-functional rooms that accommodate poor communities' social learning.